From creek to canopy: the importance of fish in Western Screech-Owl ( Megascops kennicottii ) diets in British Columbia, Canada - Megan A Buers; Frank I Doyle; Karen E. Hodges (Journal of Field Ornithology, 2025)
Being a generalist predator offers numerous advantages, including dietary flexibility that enables exploitation of abundant prey and adaptation to new habitats. However, even generalist predators may rely on specific prey during crucial life stages like reproduction. Therefore, comprehending the dietary habits of generalist predators holds significant conservation implications. In this study, we present diet and foraging observations of Western Screech-Owls ( Megascops kennicottii ) in southcentral British Columbia, Canada. Contrary to previous findings that emphasized small mammals as the primary prey in the northern part of their range, our observations highlight fish as a potentially important part of their diet. This challenges existing research and underscores the importance of considering aquatic prey in screech-owl conservation efforts. We advocate for further investigation into the ecological implications of aquatic prey consumption in their diet.